2019
DOI: 10.1186/s13104-019-4071-0
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of type III secretion system associated virulence factors (exoenzymes) in Pseudomonas aeruginosa isolated from Iranian burn patients

Abstract: ObjectiveThe present study aimed to determine the prevalence of virulence factors and antimicrobial resistance profile of Pseudomonas aeruginosa strains isolated from Iranian burn patients.ResultsThis cross-sectional study performed on 100 P. aeruginosa isolates which were recovered from burn wound specimens in 2014–2015. All presumptive isolates were identified by standard microbiologic tests. Antimicrobial susceptibility test was carried out by disk diffusion method. The presence of virulence genes was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 40 publications
4
55
1
Order By: Relevance
“…According to the literature, relationships between antimicrobial resistance and virulence traits and how they may impact the outcome of bacterial infections are a subject of growing interest [4,16,[25][26][27]. P. aeruginosa is considered one of the most problematic pathogens among Gram-negative bacteria that cause hospital infections, especially due to its extraordinary ability to acquire resistance genes and virulence [25,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, relationships between antimicrobial resistance and virulence traits and how they may impact the outcome of bacterial infections are a subject of growing interest [4,16,[25][26][27]. P. aeruginosa is considered one of the most problematic pathogens among Gram-negative bacteria that cause hospital infections, especially due to its extraordinary ability to acquire resistance genes and virulence [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to multidrug resistance, studies have shown that the type III secretion system (TTSS), which delivers effector toxins (ExoS, ExoT, ExoY and ExoU) directly into host cells [14,15], is associated with worse clinical outcomes and higher mortality rates in patients infected with P. aeruginosa [16,17]. Aggravating this scenario, some data from epidemiological studies published in the literature suggest that P. aeruginosa strains positive for the exoU gene exhibit higher multidrug resistance and more significant mortality rates than those expressing other TTSS genes [16,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…ExoS is the major virulence factor associated with invasion, colonization and spread in chronic lung infections and burns. 31 Regardless of the infection status, exoS had a higher prevalence, with only one isolate not harboring such a gene, in addition to a higher frequency than exoU in the evaluated isolates, indicating an important role in lung infection. Feltman et al 16 reported an exoS prevalence of 85% (17/20) in respiratory isolates from CF patients; however, in isolates from other clinical sources, the prevalence varied with statistical significance in relation to isolates from bloodstream infection.…”
Section: Discussionmentioning
confidence: 82%
“…13,29 Regarding T3SS-related genes, several authors have shown those variations analyzing isolates from distinct setting, including individual, environmental and clinical isolates, demonstrating the important role in the evolution of human disease and persistence in high-pressure settings. 16,17,30,31 In CF P. aeruginosa isolates, the prevalence of these genes is also variable. In a study conducted at an Iranian CF Center evaluating 143 P. aeruginosa isolates, the exoS was the most prevalent (90.2%), followed by exoU (39.8%), in addition to low frequencies of exoT (28.6%) and exoY (25.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The problem of accelerating the regeneration processes in a burn wound, suppressing wound infection, improving the results of autodermoplasty remains unsolved [3]. Despite the fact that in recent years the arsenal of means and methods used for thermal injury has significantly expanded, the results of treatment are not always satisfactory [4]. The costs of treatment of burn patients remain significant, resulting in difficulties with the long stay of patients in the hospital.…”
Section: Active Surgical Treatment Optimization Of Severe Burns R E Lmentioning
confidence: 99%